DRAMATIC MONOLOGUE IN ROBERT BROWNING’S POEM “ANDREA DEL SARTO” - Wiandari, Fadhillah (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2017)
Robert browning and the form of poetry known as â€œdramatic monologueâ€ inevitably go togather. It is already made known that dramatic monologue is esssentially a narrative spoken by a single character. We are to imagine that it is being listened to but never answered; it is a dialogue of which we are to hear only one side. It gains added effect and dimensions through the characterâ€™s comments on his own story and the circumtances in which he speaks. It is through the single characterâ€™s speech that Browning present the plot, characters and scenes. It is through the words of Andrea that the reader can feel the presence of the plot, characters and scenes. This article tries to describe how Robert Browning handles his three objects in writing dramatic monologue through his poem entitled Andrea Del Sarto.